Graph analysis from the perspective of Statistical Literacy (Research, Society and Development, 2025)
Considering the growing importance of statistical literacy in a world filled with information, this study aims to analyze the perceptions of a group of Future Researchers (FR) regarding their knowledge of graphical elements and the context in which they are embedded. From this perspective, a mixed-method approach (quantitative and qualitative-descriptive) was adopted, using data collected through an online questionnaire in 2021, with 171 validated responses. Investing in pedagogical strategies that integrate theory and scientific practice fosters situations that stimulate and develop critical thinking and data analysis. The findings indicate that most participants demonstrated an adequate understanding of basic graphical elements; however, only about 30% established a connection with the presented context. This suggests that such practices enhance the development of Statistical Literacy.